PENGARUH EKSTRAK BAWANG MERAH TERHADAP PERTUMBUHAN STUMP TANJUNG (Mimusops elengi. L) - Rifai, Muhamad; Wulandari, Retno (Universitas Tadulako, 2020)
Tanjung (Mimusops elengi. L) is a type of plant that is prospective for use in urban forest formation programs, because it has multiple functions. This study aims to determine the effect of onion extarak on the growth of cape stumps (Mimusops elengi. L). This research was conducted from January to March 2019, which was housed in the Permanent Nursery BPDAS-HL Palu-Poso Tadulako University, Palu. This study used a Completely Randomized Design (CRD) with 4 treatment concentrations of shallot extract, namely: M0 = Without Provision of Shallot Extract, M1 = Concentration of Shallot Extract 25%, M2 = Concentration of Shallot Extract 50%, M3 = Concentration of Shallot Extract 75%, and M4 = Shallot Concentration 100%. Each treatment was repeated by 10 stumps. Observations included: percentage of life, number of shoots, shoot height, and number of cape stump leaves for 2 months. Data were analyzed by analyzing variables (F test) and BNT advanced test. The results showed that the administration of shallot extra concentrations as ZPT had no significant effect on the growth of cape stumps. Provision of 75% onion concentrates gives better results on the percentage of life by 70%, the average number of shoots 2 pieces, the average shoot height of 0.966 cm, and the average number of leaves in cape stumps as much as 2.6 fruit .Keywords: Stump, Growth Regulatory Substances, Extracts, Shallots.